MEMENANGKAN PERSAINGAN BISNIS PRODUK FARMASI MELALUI MARKETING PUBLIC RELATIONS - Didik Hariyanto (Jurnal Manajemen Pemasaran, 2009)
Marketing Public Relations is one of the marketing mix that has an important role in the marketing function. Public Relations dimensions put on the effort to accommodate consumers' interests and to encourage product purchasing motivation through the credibility information. The approaches of the Marketing Public Relations are oriented on consumers’ interests, hopes, aspirations and concerns to link the impression that occur in products and companies.Marketing Public Relations and advertising are two aspects of communication that are able to complete and reinforce one another. However, in some specific situations, the Marketing Public Relations will be carried out effectively without the support of advertising. In the future, the needs of the Marketing Public Relations tend to rise increasingly based on the situation in the market currently. The relationship between Marketing Public Relations and Corporate Public Relation will be increasing, especially in facing of global marketing. The effectiveness of the Marketing Public Relations which is associated with the cost will strengthen the conclusion that the Marketing Public Relations is a communication program that is efficient and effective in order to enlarge the market share.